The experiences of military veterans prior to and during incarceration in Scottish prisons: An analysis of mental and social wellbeing - Taylor, James (2014)
Background: Concern has been voiced over the needs of ex-military personnel following their discharge from military service and subsequent transition to community living. This concern has extended to include veterans, particularly those who have mental health, drug or alcohol problems, who come into contact with criminal justice services and are imprisoned. Research examining the experiences of military veterans prior to and during their incarceration in Scottish prisons was carried out. This study sought to examine whether veteran prisoners form a unique prison sub-group with different health, social and criminogenic needs when compared to non-veteran prisoners, and how veteran prisoners differ from non-prisoner veterans. Additionally an exploration of veterans’ experiences of prison, and what they believed caused or contributed to their imprisonment, was conducted. This sought to identify whether veterans in prison had unique vulnerability/ risk factors and whether they had a common or idiographic pathway that led to their incarceration. Methods and design: This study comprised of three separate but linked parts. It adopted a mixed-method approach combining quantitative analysis of survey data (Part 1) with qualitative interpretative phenomenological analysis of focus group (Part 2) and interview data (Part 3). Survey data examined, through the use of standardised questionnaires, a range of themes; including, mental health and wellbeing, substance and alcohol use, childhood experiences, offending histories, and military experience. In Part 1 participants were recruited into three separate groups. Group 1 consisted of veterans in prison, while Group 2 consisted of prisoners who had no military experience and Group 3 comprised of Scottish Prison Service staff who had previous military experience. In Parts 2 and 3 participants were recruited from the veteran prisoner population, with participants in Part 3 having declared current mental health and/or substance use problems. Findings: Analysis of survey data identified many differences in health and wellbeing, and some differences in length of, and discharge from, military service, when comparing veteran prisoners with a non-imprisoned veteran group. Both groups, however, appeared to have similar levels of combat exposure. Comparison between veteran prisoners and non-veteran prisoners identified more similarities than differences across most of the measures. Many of the mental health drug or alcohol problems experienced by veteran prisoners were also experienced by non-veteran prisoners. Post-traumatic stress disorder did appear to be a specific problem for veteran prisoners but this did not appear to be attributable to their military experience. Additionally, veterans being raised by a mother-figure other than their birth-mother appeared to be a unique risk factor for veteran imprisonment but this finding should be viewed with caution as the number of participants raised by a mother-figure other than their birth mother was small. Findings were mixed regarding how veterans described their experience of imprisonment: some found it unchallenging yet unstimulating while others described feelings of ongoing punishment and a sense of being embattled. Reciprocal processes of dehumanising both prisoners and staff were also evident, as were contradictory experiences on the availability and quality of care provision in prison. Veteran prisoners appeared to identify with their prisoner identity rather than their veteran identity, believing that they were the same as other prisoners and had the same needs. This was evident when veterans described their experiences of forming and maintaining interpersonal relationships, albeit within-prison relationships appeared superficial in nature. While some veterans appeared reluctant to ask for assistance in prison, concerns about the inadequacies or availability of support services appear valid. Gaps in provision of care, particularly mental health care, existed at the time of the study. Lastly, some participants appeared to feel unprepared for their release from prison back to the community. This may stem from their previous experience of transitioning from the military to civilian living but it is more likely the recognition that many prisoners leave prison only to return back to custody. For some veteran prisoners this is because they believe community services are unavailable or unable to help as they struggle to cope with community living. As such, some may consider prison living the easier option. Conclusions and implications: Many of the findings suggested that veteran and non-veteran prisoners had, or were believed to have had, by veteran prisoners, similar ‘needs’ and reasons for offending. Veteran prisoners should, therefore, not be regarded as a specific sub-group of the prison population, and addressing prisoner needs should not be prioritised according to their pre-prison occupational status. Lastly, where gaps in service provision exist, the SPS and its partner agencies, including the NHS, should continue to address these. This should include giving consideration to the adoption of a trauma-informed approach within the prison environment